Higher long-term interest rates and the cost of student loans - Kate Ogden; Nick Ridpath; Ben Waltmann (Institute for Fiscal Studies (IFS), 2024)
The debate around funding student loans has largely focused on what share of student loans will be repaid, and what share of the cost will need to be picked up by the taxpayer. Much less attention has been paid to the government cost of financing student loans that do get repaid. In this report, we investigate how the cost of student loans including these financing costs has changed as a result of increases in government borrowing costs over the past two years.
Keywords: 330; Education and skills; Government finances and spending; Student finance; Education spending; Education; Government spending; Higher education; Public finance